State Control and Corporate Governance in Transition Economies: 25 Years on from 1989. (3rd December 2015) - Grosman, Anna; Okhmatovskiy, Ilya; Wright, Mike
Abstract: Manuscript type: Review Research Question/Issue: Which forms of state control over corporations have emerged in countries that made a transition from centrally‐planned to marked‐based economies and what are their implications for corporate governance? We assess the literature on variation and evolution of state control in transition economies, focusing on corporate governance of state‐controlled firms. We highlight emerging trends and identify future research avenues. Research Findings/Insights: Based on our analysis of more than 100 articles in leading management, finance, and economics journals since 1989, we demonstrate how research on state control evolved from a polarized approach of public–private equity ownership comparison to studying a variety of constellations of state capitalism. Theoretical/Academic Implications: We identify theoretical perspectives that help us better understand benefits and costs associated with various forms of state control over firms. We encourage future studies to examine how context‐specific factors determine the effect of state control on corporate governance. Practitioner/Policy Implications: Investors and policymakers should consider under which conditions investing in state‐affiliated firms generates superior returns.